Miniaturized Top-Metalized 3D-printed Rectangular Dielectric Resonator Antenna. - Herraiz Martínez, Francisco Javier; Pérez-Escribano, Mario; Sofokleous, Paris; Padilla, Pablo; Márquez-Segura, Enrique (My University, 2024)
This paper introduces a novel top-metalized Dielectric Resonator Antenna (DRA). The inclusion of top metallization induces a modification in the boundary conditions, resulting in a frequency reduction in the fundamental mode of the DRA. A prototype is designed for the 2.45-GHz WiFi band with a --10-dB bandwidth from 2.40 to 2.51 GHz. The radiation maxima occur in the top and bottom directions, with a gain of 1.81 dBi at 2.45 GHz. The proposed DRA is specifically designed for manufacturing using commercially available materials and additive manufacturing techniques.
Keywords: Antenas; Relajación dieléctrica; DRA